The relation between college students’ neuroticism and loneliness: The chain mediating roles of self-efficacy, social avoidance and distress - Li, Shuna; Kong, Kaizhen; Zhang, Kaijie; Niu, Hua (Frontiers in Psychology, 2023)
Background Recently, identifying the psychological mechanism of college students’ loneliness has attracted wide attention because the maladjustment caused by college students’ loneliness is increasingly common. This study explored the relationship and potential mechanism between college students’ neuroticism and loneliness in a large sample. Methods A total of 4,600 college students completed the Big Five Personality Scale, Loneliness Scale, Self-efficacy Scale and Social Avoidance and Distress Scale. Results By examining the chain mediating roles of self-efficacy, social avoidance and distress (SAD) in the relation between neuroticism and loneliness, the present study found that college students’ neuroticism was positively associated with loneliness via self-efficacy and SAD, respectively, and sequentially. Conclusions The results suggest a significant positive association between neuroticism and loneliness, which is influenced by the mediating effects of both self-efficacy and social avoidance and distress (SAD), as well as the chained mediating effects of self-efficacy and SAD.